Coronavirus (SARS-COV-2) in early stages of the pandemic; overview - Al-Gheethi, Adel; Noman, Efaq; Radin Mohamed, Radin Maya Saphira; Al-Maqtari, Qais; Almoheer, Reyad; Abdul-Fattah Gamal, Shaima; Hezam, Kamal; Talip, Balkis (Penerbit UTHM, 2020)
The novel coronavirus (SARS-COV-2) Pandemic has been traced in China late 2019 and then transmitted into more than 165 countries. A total of 49 papers have been published in 20 journals during the last January and current February. These papers tried to explain the source of virus, the transmission route, genomic map and the similarity to previous viruses as well as the pathogenesis, symptoms and treatment methods. The huge numbers of the articles which were published on SARS-COV-2 make confusing for the readers. In this paper a systematic analysis was conducted for the published articles. The findings of these papers were summarized. Moreover, the chapter aimed to highlight the responses of scientists and Journals for the SARS-COV-2 pandemic. This chapter reviewed 25 peer viewed articles while hundreds article still in the preprint. It was appeared that the Lancet journal given an early alarm for SARS-COV-2. The first paper suggested Baricitinib as potential treatment for SARS-COV-2 acute respiratory disease was published on 3 February. In 16 January 2020, the genomic characteristics of the virus was published, followed by several papers on the diagnostic of the virus, pathogenicity and symptoms was more clear on 29 January. The Nature Journal was the fist which given an alarm for the SARS-COV-2 pandemic. In conclusion source of SARS-COV-2, treatment methods, as well as vaccines, pathogenicity of the virus in the patient with other virus infections, transmission to fetus in the pregnant women still need more investigation.